Oczekiwanie cudu: Subiektywne konteksty doświadczenia rzeczywistości religijnej - Ciesielski, Remigiusz T. (Przegla̜d religioznawczy, 2014)
The paper attempts to describe miracle in selected areas of contemporary culture. The author, inspired by the film scenes from Pulp Fiction and Lourdes, makes an attempt to describe miracle in the consciousness of contemporary man. Through the analysis of sociological research carried out by CBOS and historian’s works dedicated to the description of miracle as well as by making use of definitions presented by Augustine and Thomas Aquinas, the author tries to identify the role of miracle in contemporary culture. In Western culture miracle happens in a reality hidden somewhere between the two aforementioned films. One and the same event can be interpreted by its receiver either as a miracle or as an accident. However, if a miracle happens and is interpreted, it brings to mind certain questions - among which is perhaps the most important one: Why did not it happen to me? Why did not I experience it?